European feelings of deprivation amidst the financial crisis: Effects of welfare state effort and informal social relations. (August 2014) - Reeskens, Tim; van Oorschot, Wim
As European governments have embraced the credo of austerity, the perennial discussion whether welfare states erode the quality of social networks has taken on a more prominent position on political and social science research agendas. While non-believers of this so-called 'crowding out' thesis argue that social networks flourish well in welfare states, believers argue that welfare provisions render social networks irrelevant in mobilizing resources. Using the 2010 wave of the European Social Survey, we analyse the extent to which both the welfare state and social networks have prevented deprivation, as well as the extent to which the functional quality of social networks in inhibiting impoverishment differs as a function of welfare state generosity. Both the 'crowding out' and the 'crowding in' theses are supported: resources are less mobilized through networks in more generous welfare states precisely because encompassing welfare provisions reduce deprivation significantly, lowering the functional quality of social networks.